2013
DOI: 10.1089/neu.2012.2650
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Consequences in a Rodent Model of Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI), particularly mild "blast type" injuries resulting from improvised exploding devices and many sport-caused injuries to the brain, result in long-term impairment of cognition and behavior. Our central hypothesis is that there are inflammatory consequences to mTBI that persist over time and, in part, are responsible for resultant pathogenesis and clinical outcomes. We used an adaptation (1 atmosphere pressure) of a well-characterized moderate-to-severe brain lateral fluid percu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
83
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 78 publications
(107 reference statements)
10
83
0
Order By: Relevance
“…The increase of Iba1 + cells seen within the cortex could be associated with the recently reported neuroprotective synaptic stripping; further analysis of the functional consequences of the observed neuroinflammation is needed [13] [37]. Perez-Polo et al [15] showed that at 6 hours after mild TBI one of the structures most affected by the pro-inflammatory cytokine IL-1β was the ipsilateral hippocampus. We previously demonstrated that treatment with low-dose methamphetamine results in decreased IL-1β expression at 32 hours after severe TBI [20].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The increase of Iba1 + cells seen within the cortex could be associated with the recently reported neuroprotective synaptic stripping; further analysis of the functional consequences of the observed neuroinflammation is needed [13] [37]. Perez-Polo et al [15] showed that at 6 hours after mild TBI one of the structures most affected by the pro-inflammatory cytokine IL-1β was the ipsilateral hippocampus. We previously demonstrated that treatment with low-dose methamphetamine results in decreased IL-1β expression at 32 hours after severe TBI [20].…”
Section: Discussionmentioning
confidence: 97%
“…Activation of microglia has been linked to neuropathologies, including chronic pain, amyotrophic lateral sclerosis (ALS) and Alzheimer's disease [6] [11] [12]. Paradoxically, activation of microglia has been linked to both neuroprotection [3] [13] and neurotoxic events [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…This excess in extracellular serotonin and glutamate availability affects neurons and astrocytes and results in over-stimulation of serotonin and glutamate receptors. It is believed that this over-stimulation effect can happen even in mild traumatic brain injury, as the release of neurotransmitters is vast even with minor lesions (Konrad et al, 2011;Perez-Polo et al, 2013). Other types of brain injury that have been reported to trigger synesthesia, such as stroke Beauchamp and Ro, 2008;Afra et al, 2009;Thomas-Anterion et al, 2010;Schott, 2012), also cause neurotransmitter flooding after necrosis.…”
Section: Acquired Synesthesiamentioning
confidence: 99%
“…Single cell measurements revealed that activity was decreased at the border of the lesion and increased in a ring around the lesion during the first days to weeks following the induction but it returned to normal after about a month (Eysel et al, 1999). Despite the fact that serotonin does not seem to stay elevated for more than one month following a brain lesion, there is suggestive evidence that the temporary elevation may suffice for creating long-lasting functional, and possibly also structural, changes (Giza and Prins, 2006;Konrad et al, 2011;Perez-Polo et al, 2013). It has furthermore been reported that initial increases in neurotransmitter levels following brain injury or disease may be followed by down-regulation of receptors in ipsilateral brain regions (Giza and Prins, 2006).…”
Section: Acquired Synesthesiamentioning
confidence: 99%
“…This suggests that the injury mechanisms might occur at very small length scales, even at the scale of a single cell. Several hypothesis have been proposed: the disruption of BBB integrity [88,43,76]; cerebral vasospasm mechanotransduced by the blast wave [3]; impairment of axonal functionality [57,58]; shock wave excitation of phonons that decay into lower frequency oscillations [49] and the formation of cavitating bubbles [71,67,66,80,109,74,37], among others.…”
mentioning
confidence: 99%